Designing Advertising: Implementation of Visual Communication Design in Marketing Communication - A. R. Yani; D. A. Nisa (Future Science)
Advertising, which is part of the creative economy, is believed by the Indonesian government as one of the sources of strength that can improve the quality of the country's economy by 2025. The advertising industry is also part of the creative economy sector which has the most gross domestic product (GDP) growth high. In order for the creative industry in Indonesia to grow and have high competitiveness, it is important for the government, especially the Ministry of Research, Technology and Higher Education (Kemenristek Dikti) to support the development of education that is capable of producing human resources who are ready to develop a creative economy in Indonesia. One effort that can be done by the Government in improving the quality of learning is to provide research assistance and publishing textbooks that are needed by students and students in the field of Visual Communication Design. If the quality of their learning increases, it certainly will have a big positive impact, one of which is to make graduates in the Visual Communication Design field have good scientific quality to build creative industrial sectors in Indonesia. Books that discuss advertising have circulated quite a lot in bookstores. However, these books discuss advertising not in the context of the implementation of advertising design in the field of Visual Communication Design. Thus, students of Visual Communication Design need a book that discusses the roles and tasks of practitioners of Visual Communication Design in the more concrete field of advertising. So this book “Mendesain Iklan” is expected to be a guide as well as a reference for students of Visual Communication Design, especially in designing advertisements.